Penerapan Prinsip Keadilan Ruang dalam Penyelenggaraan Rumah Susun Umum di Kota Yogyakarta - Amalia W (Jurnal Hukum Lex Generalis, 2025)
This study examines the implementation of the principle of spatial justice in the management of public housing in relation to the fulfillment of the rights of low-income communities to obtain decent, affordable, and equitable housing as a form of fair spatial distribution based on Law No. 20 of 2011, Government Regulation No. 13 of 2021, and existing regulations in the city of Yogyakarta. This study uses a legal-normative method with a legislative approach to examine the principle of spatial justice according to Edward Soja. The results show that the principle of spatial justice has been accommodated in these regulations. In the city of Yogyakarta, spatial justice is realized through the management and construction of several public housing complexes for low-income communities, but improvements are still needed to achieve sustainable spatial justice. Keywords: spatial justice, low-income communities, flats, low-cost flats